In vivo three‐dimensional knee kinematics in goats with unilateral anterior cruciate ligament transection. Issue 5 (13th July 2020) - Bascuñán, Ana; Soula, Mariajesus; Millar, Kristina K.; Biedrzycki, Adam; Banks, Scott A.; Lewis, Daniel D.; Kim, Stanley E.
Abstract: Although the goat is an established animal model in anterior cruciate ligament (ACL) research, in vivo kinematics associated with ACL deficiency have not been previously described in this species. Three‐dimensional knee kinematics were determined before and after unilateral ACL transection in eight goats. Fluoroscopic imaging of the knees during treadmill walking and force‐platform gait analysis during over‐ground walking were performed prior to ACL transection, and 2 weeks, 3 months, and 6 months after ACL transection. Transient lameness of the ACL‐transected limb was noted in all goats but resolved by 3 months post‐ACL transection. Increased extension of 8.7° to 17.0° was noted throughout the gait cycle in both the ACL‐transected and the contralateral unaffected knees by 3 months post‐ACL transection, in a bilaterally symmetric pattern. Peak anterior tibial translation increased by 3 to 6 mm after ACL transection and persisted over the 6‐month study period. No changes in axial rotation or abduction angle were observed after ACL transection. Unilateral ACL deficiency in goats resulted in persistent kinematic alterations, despite the resolution of lameness by 3 months post‐ACL transection.